Differentiated Instruction: A Research Basis - Subban, Pearl (International Education Journal, 2006)
With contemporary classrooms becoming increasingly diverse, educational authorities, teachers and school administrators are looking to teaching and learning strategies that cater for a variety of learning profiles. A paradigm that is gaining ground in many educational circles is differentiated instruction. This model proposes a rethinking of the structure, management and content of the classroom, inviting participants within the learning context to become engaged in the process, to the benefit of all. While the model has been accepted and set to work, there remains room for theoretical support to give it momentum. A recent, comprehensive analysis of the literature in this area examines this model, within the context of increasing academic diversity. This paper therefore seeks to synthesise the research supporting a shift to a new exemplar for modern education, and in so doing shed light on the rationale supporting differentiated instruction.
Keywords: Styles cognitifs; différenciation pédagogique; enseignement individualisé